Mycobacterium mucogenicum Hand Infection in an Intravenous Drug Abuser. (15th April 2018) - Basnet, Sijan; Mir, Izza; Dhital, Rashmi; Basnet, Garima; Patel, Nitin
Abstract : Mycobacterium mucogenicum is a rapidly growing mycobacterium found ubiquitously in water sources. It has been reported to cause widespread infections with infection entry from wound or central venous catheters especially in immunocompromised patients. Diagnosis is made from blood cultures which may take at least a week. Management includes removal of the source or drainage of wound infections and combination antimicrobial therapy.